Coherence contributions to the entropy production in quantum processes - Cipolla, Mariana Afeche (2021)
The thermodynamics of quantum processes is a recent field of study and it has been growing in recent years. Previously thought of as an emergent phenomenon for macroscopic systems, thermodynamics started being applied to quantum systems considering quantities such as heat and work as stochastics. The peculiarity of these systems is that, in addition to studying energetic resources, we must also take into account quantum informational resources such as entanglement and coherence. In this scenario, entropy becomes an important quantity, because in addition to being related to the irreversibility of a process, it can also be used as a measure of the amount of information in the system to which we have access. Entropy, unlike energy, is not a conserved quantity; that is, in a closed system, there is not only an entropy flow between it\'s parts, but also, in general, entropy production. According to the principle of Landauer [IBM Journal of Research and Development, vol. 5, no. 3, pp. 183191 (1961)], it is the entropy produced that causes the loss of information. Studying, then, the production of entropy becomes important for areas such as quantum computing, where you want to have control over information gains and losses. In quantum processes, entropy is produced due both to changes in the energy of the system and to fluctuations in coherence [Phys. Rev. E 99, 042105 (2019); npj Quantum Information 5, 23 (2019)], a purely quantum resource. In this project, we propose to study the statistics of entropy production due to coherence. For this, we will investigate two different splittings of the entropy production: the one proposed in [Phys. Rev. E, vol. 99, 042105 (2019); npj Quantum Information 5, 23 (2019)] and a most recent one proposed in [Phys. Rev. Research 2, 023377 (2020); New Journal of Physics 23, 063027 (2021)]. For simplicity, we will analyse a unitary quantum process, using the two-point measurement (TPM) scheme [Phys. Rev. E 75, 050102 (2007)]. We will apply both formalisms for two specific quantum systems: a macrospin model and the Lipkin-Meshkov-Glick (LMG) model [Nuclear Physics, vol. 62, no. 2, pp. 188 224 (1965)]. We will analyse, in these cases, how the distribution of coherence depends on parameters such as system dimension, temperature, evolution in time, etc.